Proceedings of the 21st Annual Meeting of the European Society for Animal Cell Technology (ESACT), Dublin, Ireland, June 7-10, 2011
DOI: 10.1007/978-94-007-0884-6_78
|View full text |Cite
|
Sign up to set email alerts
|

Flow Characterization in Wave Bioreactors Using Computational Fluid Dynamics

Abstract: Quantifying and optimizing the flow conditions in cultivation systems is essential for successful cell growth in major biotechnological applications, like vaccine production processes. Recently, disposable wave bioreactors have been proposed for manufacturing of biologics, leading to markedly different mixing properties compared to stirred tank reactors, i.e. lower shear stress. To describe accurately the conditions in wave bioreactors using numerical simulations, it is first necessary to compute the unsteady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…The calculated Reynolds number, based on the definition presented in Equation , ranged from a low of 4,114 at 3L, 8° rocking angle and 10 rpm rocking speed to a high value of 27,435 at 10 L, 12° rocking angle and 40 rpm. This range was higher than in previously reported works due to the different definition used in this study, as well as a wider range of used experimental conditions (Eibl et al, ; Marsh et al, ; Öncül et al, ).…”
Section: Resultscontrasting
confidence: 52%
See 2 more Smart Citations
“…The calculated Reynolds number, based on the definition presented in Equation , ranged from a low of 4,114 at 3L, 8° rocking angle and 10 rpm rocking speed to a high value of 27,435 at 10 L, 12° rocking angle and 40 rpm. This range was higher than in previously reported works due to the different definition used in this study, as well as a wider range of used experimental conditions (Eibl et al, ; Marsh et al, ; Öncül et al, ).…”
Section: Resultscontrasting
confidence: 52%
“…Though so far no experimental measurement of linear phase velocity in a wave bioreactor has been reported, there are some related works available for comparison which characterized either the averaged or temporal and spatial liquid velocity. Öncül et al () reported from their CFD simulation that the mean velocity fluctuated between 0.1 and 0.3 m/s (average approximately 0.2 m/s), passing through the center line of a 20 L bag (7 L liquid volume) at 15 rpm and a 7° angle. Kalmbach et al () later confirmed this value in their hot‐wire anenometry experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation